2009
DOI: 10.1021/nl8026857
|View full text |Cite
|
Sign up to set email alerts
|

Nanowires for Enhanced Boiling Heat Transfer

Abstract: Boiling is a common mechanism for liquid−vapor phase transition and is widely exploited in power generation and refrigeration devices and systems. The efficacy of boiling heat transfer is characterized by two parameters: (a) heat transfer coefficient (HTC) or the thermal conductance; (b) the critical heat flux (CHF) limit that demarcates the transition from high HTC to very low HTC. While increasing the CHF and the HTC has significant impact on system-level energy efficiency, safety, and cost, their values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
412
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 612 publications
(435 citation statements)
references
References 28 publications
14
412
1
6
Order By: Relevance
“…Nanostructures have been reported to improve differing aspects of the boiling process (e.g., incipience, nucleation boiling, and critical heat flux) via CNT-coating of silicon [211][212][213] and copper substrates [80,213], and copper nanowire [214][215][216] and silicon nanowire [215][216][217] surface coatings.…”
Section: Nanostructured Capillary Wicks For Vapor Chamber Applicationsmentioning
confidence: 99%
“…Nanostructures have been reported to improve differing aspects of the boiling process (e.g., incipience, nucleation boiling, and critical heat flux) via CNT-coating of silicon [211][212][213] and copper substrates [80,213], and copper nanowire [214][215][216] and silicon nanowire [215][216][217] surface coatings.…”
Section: Nanostructured Capillary Wicks For Vapor Chamber Applicationsmentioning
confidence: 99%
“…A similar analysis has been employed by others with satisfactory predictions [17,34]. Using a volumetric porosity ε of 0.5±0.02, an average breakthrough bubble diameter d br of 42 μm (determined from the average pore diameter ), and thermophysical properties of water at saturation temperature (100 °C), the hydrodynamic limit of the bare sample is estimated to be 906±102 W/cm 2 using: …”
Section: Mechanism Of Dryoutmentioning
confidence: 91%
“…Liter and Kaviany [34] demonstrated that the hydrodynamic limit can be significantly increased using modulated porous structures which provide preferential flow paths for liquid and vapor, thereby reducing the liquid/vapor counterflow situations and aiding non-hydrodynamical determination of the critical instability wavelength. Various other studies also report a significant increase in critical heat flux (CHF) of uniformly coated porous surfaces compared to plain surfaces investigated under natural convection boiling conditions [17,35]. Reasons for this reported enhancement include heat transfer from extended surfaces, an increase in nucleation site density, and enhanced lateral liquid replenishment to the active nucleation sites via capillary action that reduces the liquid-vapor counterflow resistance.…”
Section: Mechanism Of Dryoutmentioning
confidence: 96%
See 1 more Smart Citation
“…Solid-liquid-vapor interfaces controlled by the TCL exist widely in multiphase interfaces systems, which is important in biological [36] and industrial processes. [37] Numerous papers report static state [38] and dynamic state [9d,39] aspects of the exterior TCL on textured surfaces. However, a few quantitative methods for the direct nanoscale visualization of the 3D droplet and underlying substrate interface result from the low resolution of measurement techniques.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%